Gulf War and Health: Volume 5: Infectious Diseases - Institute of Medicine (The National Academies Press, 2007)
Infectious diseases have been a problem for military personnel throughout history. The consequences in previous conflicts have ranged from frequent illnesses disrupting daily activities and readiness to widespread deaths. Preventive measures, early diagnosis, and treatment greatly limit the exposures and acute illnesses of troops today in comparison with those in armies of the past, but infections and consequent acute illnesses still occur. Thousands of US veterans of the Persian Gulf War have reported an array of unexplained illnesses since the war ended in 1991. Many veterans have believed that the illnesses were associated with their military service in southwest Asia during the war. This volume of Gulf War and Health evaluates the scientific literature on chemical, biologic, and physical agents to which military personnel in the gulf were potentially exposed and possible long-term adverse health outcomes.

Informing the Future: Critical Issues in Health, Fifth Edition - Institute of Medicine; Institute of Medicine (The National Academies Press, 2009)
Today, perhaps more than ever, health care is a key item on the nation's agenda. Government policy makers, health professionals, scientists, industrial and civic leaders, patient advocates, and private citizens across the social spectrum are focusing on how best to obtain a high-quality health system that is efficient and affordable in its operation and that functions well for everyone. The Institute of Medicine (IOM) regularly considers this challenge from a variety of perspectives. Recent efforts have focused on improving the organization and operation of the nation's largest health agency; working to assess what diagnostic, therapeutic, and preventive services work best; gauging the overall health of the nation's population; and identifying ways to build an even stronger foundation of evidence-based medicine that effectively captures the promise of scientific discovery and technological innovation and enables doctors, nurses, and other health professionals to provide the right care for the right patient at the right time. The body of this book illustrates the work of IOM committees in selected, major areas in recent years, followed by a description of IOM's convening and collaborative activities and fellowship programs. The last section provides a comprehensive bibliography of IOM reports published since 2007.

Informing the Future: Critical Issues in Health, Sixth Edition - Institute of Medicine (The National Academies Press, 2011)
This report illustrates the work of IOM committees in selected, major areas in recent years, followed by a description of IOM's convening and collaborative activities and fellowship programs. The last section provides a comprehensive bibliography of IOM reports published since 2007.

Informing the Future: Critical Issues in Health: Fourth Edition - Institute of Medicine (The National Academies Press, 2007)

Amyotrophic Lateral Sclerosis in Veterans: Review of the Scientific Literature - Institute of Medicine (The National Academies Press, 2006)
Amyotrophic lateral sclerosis (ALS) our Lou Gehrig's disease is a fatal, mostly non-familial disease that affects the nervous system of humans by causing the degeneration of nerve cells in the brain and spinal cord. The degeneration halts communication between the nervous system and voluntary muscles in the body. This leads to muscle paralysis and eventually the muscles that aid in breathing are affect; causing respiration to fail. The disease, which affects 20,000-30,000 men and women in the United States at any given time, has no effective treatment; most people with ALS die from respiratory failure within 5 years of the onset of symptoms. Recent epidemiologic studies report an association between the development of ALS and prior service in the U.S. military. The studies evaluated either veterans of the 1991 Persian Gulf War or veterans who served in the military in the period 1910-1982. Due to these findings, the Department of Veterans Affairs (VA) asked the National Academies to conduct an assessment of the potential relationship between military service and the later development of ALS. The project was assigned to the Institute of Medicine (IOM), which appointed a committee and gave it the task of evaluating the scientific literature on ALS in veterans. The committee began its work by identifying medical and scientific literature on ALS. PubMed, a database created and managed by the National Library of Medicine. Amyotrophic Lateral Sclerosis in Veterans; Review of the Scientific Literature presents the findings of this committee. The committee reviewed, evaluated, and summarized the scientific literature on ALS in veterans, composed primarily of peer-reviewed, published literature. This report includes the recommendations of the committee.

Gulf War and Health: Volume 8: Update of Health Effects of Serving in the Gulf War - Institute of Medicine (The National Academies Press, 2010)
For the United States, the 1991 Persian Gulf War was a brief and successful military operation with few injuries and deaths. However, soon after returning from duty, a large number of veterans began reporting health problems they believed were associated with their service in the Gulf. At the request of Congress, the IOM is conducting an ongoing review of the evidence to determine veterans' long-term health problems and what might be causing those problems. The fourth volume in the series, released in 2006, summarizes the long-term health problems seen in Gulf War veterans. In 2008, the IOM began an update to look at existing health problems and identify possible new ones, considering evidence collected since the initial summary. In this report, the IOM determines that Gulf War service causes post-traumatic stress disorder (PTSD) and that service is associated with multisymptom illness; gastrointestinal disorders such as irritable bowel syndrome; alcohol and other substance abuse; and anxiety disorders and other psychiatric disorders. To ensure that our veterans receive the best possible care, now and in the future, the government should continue to monitor their health and conduct research to identify the best treatments to assist Gulf War veterans still suffering from persistent, unexplained illnesses.

Gulf War and Health: Updated Literature Review of Depleted Uranium - Institute of Medicine (The National Academies Press, 2008)
The 1991 Persian Gulf War was considered a brief and successful military operation with few injuries and deaths. A large number of returning veterans, however, soon began reporting health problems that they believed to be associated with their service in the gulf. Under a Congressional mandate, the Institute of Medicine (IOM) is reviewing a wide array of biologic, chemical, and physical agents to determine if exposure to these agents may be responsible for the veterans' health problems. In a 2000 report, Gulf War and Health, Volume 1: Depleted Uranium, Sarin, Pyridostigmine Bromide, and Vaccines, the IOM concluded that there was not enough evidence to draw conclusions as to whether long-term health problems are associated with exposure to depleted uranium, a component of some military munitions and armor. In response to veterans' ongoing concerns and recent publications in the literature, IOM updated its 2000 report. In this most recent report, Gulf War and Health: Updated Literature Review of Depleted Uranium, the committee concluded that there is still not enough evidence to determine whether exposure to depleted uranium is associated with long-term health problems. The report was sponsored by the U.S. Department of Veterans Affairs.

Gulf War and Health: Volume 9: Long-Term Effects of Blast Exposures - Institute of Medicine (The National Academies Press, 2014)
Since the United States began combat operations in Afghanistan in October 2001 and then in Iraq in March 2003, the numbers of US soldiers killed exceed 6,700 and of US soldiers wounded 50,500. Although all wars since World War I have involved the use of explosives by the enemy, the wars in Afghanistan and Iraq differ from previous wars in which the United States has been involved because of the enemy's use of improvised explosive devices (IEDs). The use of IEDs has led to an injury landscape different from that in prior US wars. The signature injury of the Afghanistan and Iraq wars is blast injury. Numerous US soldiers have returned home with devastating blast injuries and they continue to experience many challenges in readjusting to civilian life. Gulf War and Health, Volume 9 is an assessment of the relevant scientific information and draws conclusions regarding the strength of the evidence of an association between exposure to blast and health effects. The report also includes recommendations for research most likely to provide VA with knowledge that can be used to inform decisions on how to prevent blast injuries, how to diagnose them effectively, and how to manage, treat, and rehabilitate victims of battlefield traumas in the immediate aftermath of a blast and in the long term.

Gulf War and Health: Volume 7: Long-Term Consequences of Traumatic Brain Injury - Institute of Medicine (The National Academies Press, 2009)
The seventh in a series of congressionally mandated reports on Gulf War veterans health, this volume evaluates traumatic brain injury (TBI) and its association with long-term health affects. That many returning veterans have TBI will likely mean long-term challenges for them and their family members. Further, many veterans will have undiagnosed brain injury because not all TBIs have immediately recognized effects or are easily diagnosed with neuroimaging techniques. In an effort to detail the long term consequences of TBI, the committee read and evaluated some 1,900 studies that made up its literature base, and it developed criteria for inclusion of studies to inform its findings. It is clear that brain injury, whether penetrating or closed, has serious consequences. The committee sought to detail those consequences as clearly as possible and to provide a scientific framework to assist veterans as they return home.

Gulf War and Health: Volume 10: Update of Health Effects of Serving in the Gulf War, 2016 - Institute of Medicine; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2016)
For the United States, the 1991 Persian Gulf War was a brief and successful military operation with few injuries and deaths. However, soon after returning from duty, a large number of veterans began reporting health problems they believed were associated with their service in the Gulf. At the request of Congress, the Institute of Medicine (IOM) has been conducting an ongoing review of the evidence to determine veterans' long-term health problems and potential causes. The fourth volume in the series, released in 2006, summarizes the long-term health problems seen in Gulf War veterans. In 2010, the IOM released an update that focuses on existing health problems and identifies possible new ones, considering evidence collected since the initial summary. Gulf War and Health: Volume 10 is an update of the scientific and medical literature on the health effects associated with deployment to the Gulf War that were identified in Volumes 4 and 8. This report reviews and evaluates the associations between illness and exposure to toxic agents, environmental or wartime hazards, or preventive measures and vaccines associated with Gulf War service, and provides recommendations for future research efforts on Gulf War veterans.

Gulf War and Health: Volume 6: Physiologic, Psychologic, and Psychosocial Effects of Deployment-Related Stress - Institute of Medicine (The National Academies Press, 2008)
The sixth in a series of congressionally mandated reports on Gulf War veterans' health, this volume evaluates the health effects associated with stress. Since the launch of Operation Desert Storm in 1991, there has been growing concern about the physical and psychological health of Gulf War and other veterans. In the late 1990s, Congress responded by asking the National Academy of Sciences (NAS) to review and evaluate the scientific and medical literature regarding associations between illness and exposure to toxic agents, environmental or wartime hazards, and preventive medicines or vaccines in members of the armed forces who were exposed to such agents. Deployment to a war zone has a profound impact on the lives of troops and on their family members. There are a plethora of stressors associated with deployment, including constant vigilance against unexpected attack, difficulty distinguishing enemy combatants from civilians, concerns about survival, caring for the badly injured, and witnessing the death of a person. Less traumatic but more pervasive stressors include anxiety about home life, such as loss of a job and income, impacts on relationships, and absence from family. The focus of this report, by the Institute of Medicine (IOM) Committee on Gulf War and Health: Physiologic, and Psychosocial Effects of Deployment-Related Stress, is the long-term effects of deployment-related stress. Gulf War and Health: Volume 6. Physiologic, and Psychosocial Effects of Development Related Stress evaluates the scientific literature regarding association between deployment-related stressors and health effects, and provides meaningful recommendations to remedy this problem.

Gulf War and Health: Treatment for Chronic Multisymptom Illness - Institute of Medicine (The National Academies Press, 2013)
Chronic multisymptom illness (CMI) is a serious condition that imposes an enormous burden of suffering on our nation's veterans. Veterans who have CMI often have physical symptoms (such as fatigue, joint and muscle pain, and gastrointestinal symptoms) and cognitive symptoms (such as memory difficulties). For the purposes of this report, the committee defined CMI as the presence of a spectrum of chronic symptoms experienced for 6 months or longer in at least two of six categories2014fatigue, mood, and cognition, musculoskeletal, gastrointestinal, respiratory, and neurologic2014that may overlap with but are not fully captured by known syndromes (such as CFS, fibromyalgia, and IBS) or other diagnoses. Despite considerable efforts by researchers in the United States and elsewhere, there is no consensus among physicians, researchers, and others as to the cause of CMI. There is a growing belief that no specific causal factor or agent will be identified. Many thousands of Gulf War veterans1 who have CMI live with sometimes debilitating symptoms and seek an effective way to manage their symptoms. Estimates of the numbers of 1991 Gulf War veterans who have CMI range from 175,000 to 250,000 (about 25-35% of the 1991 Gulf War veteran population), and there is evidence that CMI in 1991 Gulf War veterans may not resolve over time. Preliminary data suggest that CMI is occurring in veterans of the Iraq and Afghanistan wars as well. In addition to summarizing the available scientific and medical literature regarding the best treatments for chronic multisymptom illness among Gulf War veterans, Gulf War and Health: Volume 9: Treatment for Chronic Multisymptom Illness recommends how best to disseminate this information throughout the VA to improve the care and benefits provided to veterans, recommends additional scientific studies and research initiatives to resolve areas of continuing scientific uncertainty and recommends such legislative or administrative action as the IOM deems appropriate in light of the results of its review.

Improving the Presumptive Disability Decision-Making Process for Veterans - Institute of Medicine
The United States has long recognized and honored the service and sacrifices of its military and veterans. Veterans who have been injured by their service (whether their injury appears during service or afterwards) are owed appropriate health care and disability compensation. For some medical conditions that develop after military service, the scientific information needed to connect the health conditions to the circumstances of service may be incomplete. When information is incomplete, Congress or the Department of Veterans Affairs (VA) may need to make a \

Gulf War and Health: Volume 11: Generational Health Effects of Serving in the Gulf War - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2018)
For the United States, the 1991 Persian Gulf War was a brief and successful military operation with few injuries and deaths. However, soon after returning from duty, a large number of veterans began reporting health problems they believed were associated with their service in the Gulf. At the request of Congress, the National Academies of Sciences, Engineering, and Medicine has been conducting an ongoing review of the evidence to determine veterans' long-term health problems and potential causes. Some of the health effects identified by past reports include post-traumatic stress disorders, other mental health disorders, Gulf War illness, respiratory effects, and self-reported sexual dysfunction. Veterans' concerns regarding the impacts of deployment-related exposures on their health have grown to include potential adverse effects on the health of their children and grandchildren. These concerns now increasingly involve female veterans, as more women join the military and are deployed to war zones and areas that pose potential hazards. Gulf War and Health: Volume 11 evaluates the scientific and medical literature on reproductive and developmental effects and health outcomes associated with Gulf War and Post-9\/11 exposures, and designates research areas requiring further scientific study on potential health effects in the descendants of veterans of any era.